POTENTIAL OF GARDEN WASTE AS RENEWABLE ENERGI USING CATALYTIC PYROLYSIS, CASE STUDY BANDUNG CITY - HASFITA, FiKRI
The increasing number of city parks has caused the amount of waste generation from the urban sector to become uncontrollable. On the other hand, the scarcity of energy sourced from fossil energy has had an impact on people’s social lives. Several policies have been pursued in order to overcome the energy crisis including finding new renewable energy sources that can be used sustainably. Garden waste has the potential to be developed as a renewable energy source. This research examines aspects of novelty in scientific development in the field of urban park waste management technology which includes aspects of waste generation, technology use, potential energy and electrical power and energy contribution in achieving the New Renewable Energy target. The research was conducted in two stages, namely field survey and laboratory scale. The field survey consisted of observations of waste generation, composition and characteristics of city park waste as a basis for laboratory-scale research. The types of waste consisted of leaf waste and plastic waste from ten thematic parks in Bandung City. The laboratory-scale research is an application of catalytic pyrolysis technology that aims to convert garden waste into energy products. The process takes place under batch conditions using a fixed bed reactor at a temperature variation of 100-500oC, sample weight of 50-200 grams, process using catalyst and without catalyst. Analysis of the pyrolysis process consists of yield values and product characteristics, mass balance and conversion, energy balance and efficiency, pyrolysis process kinetics, electrical potential and energy contribution in achieving EBT targets. Analysis of waste generation, composition and characterization aims to assess the potential for using garden waste as renewable energy by analyzing the amount of generation based on parks, seasons, number of trees and park area for leaf waste, and the amount of generation based on parks, seasons, visiting times consisting of the beginning of the week and weekends as well as the number of visitors for visitor waste. Waste characteristics are analyzed using proximate and ultimate methods, composition analysis, and elemental analysis using XRF (X-Ray Fluorescence). The research results show that the type of park, number of trees, season, number of visitors, significantly influence the generation of Bandung City park waste. The composition of park waste consists of 91.18% leaf waste, 8.6% visitor waste and 0.22% other types of waste. Average leaf waste generation is 44.65 ± 2.20 kg/park/day with a number of trees 10-270 and visitor waste generation is 4.8 kg/park/day or 0.13 kg/person/day with an average number of visitors -average 35 people. The composition of visitor waste is dominated by plastic bag waste, reaching 38%. Analysis of the chemical components of leaf waste consists of 21.87% cellulose, 10.17% hemicellulose and 10.20% lignin, 0.30% sulfur content, 40.45% carbon and 83.08% volatile content. Elemental analysis using XRF resulted in the largest component in leaf waste being the element Ca (calcium) 51.6% and the calorific value of leaf waste was 3612 kcal/kg. The pyrolysis process produces three types of energy products consisting of charcoal, bio-oil and gas. The variables analyzed consist of: the influence of temperature, biomass weight and catalyst on the yield of pyrolysis products. The product is characterized by analyzing the heating value, FTIR analysis, SEM analysis, GC-MS, XRF, ultimate analysis and proximate analysis. Based on the temperature, the highest charcoal yield was 92 - 96%, with a temperature of 100 - 200 oC in the process without a catalyst, the highest bio-oil yield was 13% - 22% at a temperature of 200-300 oC. Meanwhile, 20 – 83% gas was obtained at a temperature of 100-500 oC in the catalyzed process with a sample weight of 50-200 grams. The calorific value of leaf waste increased from 3612 kcal/kg for waste without pyrolysis to 8876.5 kcal/kg for bio-oil and charcoal was obtained at 6000.8 kcal/kg in the catalysis process. FTIR analysis showed that the OH groups and aliphatic CH groups were related to phenol and carboxylic acid. SEM analysis shows that leaf waste charcoal has large pores. GC-MS analysis of bio-oil from leaf waste was dominated by Phenol (C6H6O) 9.0%, Cresol, (C7H8O) 9.4%, 11,2,3- Trimethylbenzene (C9H12) 9.9%, 1- methyl-2-cyclopropen-1 (C9H18) 9.5%, exadecanoic acid (C16H32O2) 10.7%, while plastic waste is dominated by furan compounds 8.8%, Cyclohexane 3.9%, 1,3-trimethylcyclopentylamine 5, 0%, nhexanoy 4% 4'-dimethoxyphenyl 4.7%, 2-p-Nitrophenyl-oxadiazol-1 3.5%. XRF analysis of leaf waste contains the mineral elements Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, Mn, Fe, Co, Zn, Rb, Sr and Pb. Plastic waste samples consist of Al, Si, P, S, Cl, K, Ca, Ti, Fe, Cu, Zn, Zr, and Pb, mineral analysis does not show elements that are harmful to the environment. Leaf waste charcoal has a low sulfur content of 4.0%, indicating that garden waste has the potential to be developed into a source of renewable energy. To analyze the performance of the pyrolysis process, the mass and energy balance is studied based on the input mass and energy as well as the output mass and energy during the pyrolysis process, then the kinetic parameters are determined which consist of the reaction rate constant, activation energy and the kinetic equation obtained from the results of the graph plot between temperature (1/T) with the reaction constant (k). Conversion is determined based on the number of solid samples that are converted into products, while energy efficiency is the ratio of the amount of output energy to input energy. Maximum conversion was obtained on the activation catalyst with 25 grams of solid sample remaining, 15 grams of liquid and 160 grams of gas, 87% conversion at a sample weight of 200 grams, temperature 500oC. The addition of plastic was able to increase the liquid product to a maximum of 55 grams in the catalyst activation process at a temperature of 400oC with a sample weight of 200 grams. Maximum product energy was obtained from garden waste in the form of charcoal, bio-oil and gas, 7115 kJ/gram, at a temperature of 100 – 500oC, weighing 50 – 200 grams. The energy required for the process is 5940 kJ with a process efficiency of 79.37%. Kinetic analysis shows that the process without a catalyst produces an activation energy of 1786 – 2136 kJ/gram, the catalyzed process 1168 – 1508 kJ/gram, and the activation catalyst 1138 – 1453 kJ/gram, which shows the catalyst lowers the activation energy. Determining the electricity potential and energy contribution in achieving the EBT target aims to analyze the amount of electrical power produced from green open spaces as a source of municipal waste-powered generation. Electrical power potential is analyzed based on the type of park, the amount generated by each park, the pyrolysis process and without pyrolysis. The results obtained show the electricity potential of Bandung City's garden waste with an average amount of leaf waste generation of 44.65 kg/day/garden producing 0.193 MW of power for waste without pyrolysis with a potential contribution to the EBT target of 0.000033 MW. Meanwhile, the electricity potential with the catalytic pyrolysis process produces 0.33 MW of power with a potential contribution to the EBT target of 0.000057 MW. Visitor waste with generation of 4.81 kg/day/park produces 0.037 MW of power for waste without pyrolysis with a potential contribution to the EBT target of 0.0000064 MW. Meanwhile, the electricity potential with the catalytic pyrolysis process produces 0.044 MW of power with a potential contribution to the EBT target of 0.0000076 MW. The pyrolysis process increases the energy potential of city park waste and reduces waste from the source, so it has the potential to be developed in sustainable management of city park waste.